The Role of State Administrative Law in Realizing Effective and Efficient Public Services - Nurlina Ritonga; Nabila Rojak; Anisa Nst; Khoiriah Ismaini; Siti Nurhaliza; Teguh Sangkot Hasibuan; Asri Amanda Putri; Intan Sopiah; Frian Wardani (Manunggal Halim Jaya, 2026)
Administrative Law plays a central role in regulating, supervising, and ensuring the implementation of effective and efficient public services. This study aims to analyze the contribution and role of administrative law in creating responsive, transparent, and accountable public services. The research employs a qualitative method with a descriptive-analytical approach, utilizing data from statutory regulations, academic literature, and previous studies. The findings reveal that the application of administrative law principles, such as legal certainty, accountability, proportionality, and transparency, significantly improves the quality of public services. Furthermore, the strict enforcement of legal norms on government officials fosters greater professionalism within the bureaucracy and minimizes maladministration and corruption. However, challenges such as weak law enforcement, limited human resource cotence, and resistance to change remain obstacles to the optimization of public services. This study emphasizes that administrative law reform, capacity building of government officials, and the strengthening of oversight systems are strategic measures required to ensure the realization of effective and efficient public service delivery. The findings are expected to serve as a reference for policymakers and government practitioners in formulating policies and strategies for improving public service delivery in Indonesia.